Decree of the President of the Republic No. 478 of the year 2016 On Establishing the Supreme Council for Investment = قرار رئيس جمهورية مصر العربية رقم 478 لسنة 2016 بإنشاء المجل الأعلى للاستثمار - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic